Effective Treatment of Secondary Hypogonadism with Clomiphene Citrate in a Male Patient with Secondary Polycythemia and History of Transient Ischemic Attack: A Case Report - A. Manov; A. Hatharasinghe; S. Acaralp (New Frontiers in Medicine and Medical Research Vol. 10, 2021)
We are describing the patient with hypogonadism who developed polycythemia and transient ischemic attacks due to Testosterone replacement therapy. We treated the patient successfully with Clomiphene- selective estrogen modulator which increases the GnRH secretion by hypothalamus and subsequently gonadotropins from the anterior pituitary gland. Clomiphene was not associated with Polycythemia and was tolerated by the patient well.